Beyond the scalpel – mortality after liver surgery in patients with liver metastases – time to rethink the indications. Issue 1 (23rd December 2019) - Boda‐Heggemann, J.; Hofheinz, R.; Gkika, E.; Brunner, T.; Krug, D.
Abstract : Comment to Filman et al., Mortality after liver surgery in Germany. Br J Surg, 2019.